2022
DOI: 10.26596/wn.202213421-28
|View full text |Cite
|
Sign up to set email alerts
|

Double burden of malnutrition among mothers and their under five children in rural areas of Oyo State, Nigeria

Abstract: Background/Objective: Double burden of malnutrition, characterized by undernutrition among poor children and overnutrition among disadvantaged adults coexisting in the same population group or household, is a serious global problem. The objective of this study was to assess double burden of malnutrition among mothers and their under-five children in rural communities of Ibadan, Nigeria. Methods: This cross-sectional and descriptive study adopted a two-stage random sampling to recruit 217 mother-child pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…The results also showed that majority of the respondents were married 195 (68.7%). This is in agreement with previous studies [26,27,29,30]. This present study also revealed that majority of the respondents 164 (57.8%) had good knowledge of hypertension while 18 (6.3%) did not have any knowledge of hypertension at all.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results also showed that majority of the respondents were married 195 (68.7%). This is in agreement with previous studies [26,27,29,30]. This present study also revealed that majority of the respondents 164 (57.8%) had good knowledge of hypertension while 18 (6.3%) did not have any knowledge of hypertension at all.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study revealed that majority of the respondents were males 154 (54.2%). This is in tandem with the findings of Adeyanju et al, [26] but at variance with the findings of Aliko et al, [25]; Akpa et al, [27], and Wokoma et al, [28]. These studies which were all on hypertension were carried out in Rivers State.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, breastfeeding and other nutritional strategies must consider the parent's educational level and poverty status. Dual malnutrition was found in other studies, particularly in Africa, where the factors listed were much more similar ( 144 ).…”
Section: Discussionsupporting
confidence: 67%